2018
DOI: 10.1002/rhc3.12161
|View full text |Cite
|
Sign up to set email alerts
|

Preparing for Disaster: Social Media Use for Household, Organizational, and Community Preparedness

Abstract: Social media applications provide conduits for government agencies to promote disaster preparedness. This article illustrates the messaging strategies used by state‐level emergency management agencies in the United States and addresses a range of social units (e.g., households, organizations, and communities). While agencies frequently disseminate guidance on how to prepare for emergencies, strategies generally align with traditional government‐to‐citizen, one‐to‐many communication modes characterized by littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Scholarship describes social media campaigns that inform communities on what to expect from specific hazards (e.g., hurricanes, earthquakes, and wildfires) and how to prepare households and organizations within their jurisdictions (Wukich, 2016(Wukich, , 2019. During disasters, specific guidance on what to do constitutes coproduction prompts as well.…”
Section: As Partnersmentioning
confidence: 99%
“…Scholarship describes social media campaigns that inform communities on what to expect from specific hazards (e.g., hurricanes, earthquakes, and wildfires) and how to prepare households and organizations within their jurisdictions (Wukich, 2016(Wukich, , 2019. During disasters, specific guidance on what to do constitutes coproduction prompts as well.…”
Section: As Partnersmentioning
confidence: 99%
“…In some cases, the widespread adoption and use of such tools outpaced both the government's use and message content. For instance, Wukich (2019) showed that while agencies increasingly instruct their audiences through social media on how to prepare for emergencies, their strategies generally anticipate and include little to no interaction with the public in line with traditional government-to-citizen, one-to-many communication modes. In the future, we may expect a surge in studies focusing on the role of artificial intelligence and its application in crisis communication, along with efforts to debunk disinformation and rumors.…”
Section: Discussionmentioning
confidence: 99%
“…Some social media enjoy more direct attention by formal actors (such as U.S. president Trump) than their traditional counterparts, for political and blame management purposes. Social media incorporate a wider range of users, including citizens beyond the reach of newspapers and national television, such as teenagers but also potential voters (Wukich, 2019). Social media platforms have become useful tools for actors seeking to construct or spread fake or misrepresented news with the aim of influencing a specific issue or process, sometimes with political purposes.…”
Section: Mediamentioning
confidence: 99%